Upaya Peningkatan Kinerja Guru Melalui Teknik Lesson Study Secara Kolaboratif dan Rutin - Punguan Siregar (JURNAL GLOBAL EDUKASI, 2022)
Abstract: The background of this research is to address and correct wrong patterns of thinking by providing guidance/guidance for school-based teachers called (Lesson Study) in a collaborative and sustainable manner based on the principles of collegiality and mutual learning to build a learning community, to equip teachers to carry out their duties as learning agent. This school action research was conducted at SD Negeri 13 Hutanamora. The results of the study showed that the teacher's mastery in conducting learning increased from the first cycle to the second cycle after being given routine short briefing techniques regarding the correct preparation of lesson plans, subject matter to be delivered from cycle to cycle. Cycle I achieved an average score of 26.5 Cycle II achieved 33. It was concluded that routine and continuous program implementation is the key to success in carrying out duties as a school principal in improving the quality of learning in the classroom. In an effort to improve teacher performance through collaborative and routine Lesson Study techniques, SD Negeri 13 Hutanamora was able to form productive/professional teaching staff and was able to improve the quality of learning. Keywords: collaborative; lesson study; teacher performance  Abstak: Penelitian ini dilatarbelakangi untuk menyikapi sekaligus memperbaiki pola-pola pemikiran yang salah dengan memberikan pengarahan/pembinaan guru berbasis sekolah yang dinamakan dengan (Lesson Study) secara kolaboratif dan berkelanjutan berlandaskan prinsip-prinsip kolegalitas dan mutual learning untuk membangun komunitas belajar, untuk membekali guru dalam melaksanakan tugasnya sebagai agen pembelajaran. Penelitian Tindakan Sekolah ini dilakukan di SD Negeri 13 Hutanamora. Hasil penelitian diperoleh bahwa penguasaan guru dalam melakukan pembelajaran mengalami peningkatan dari siklus pertama ke siklus kedua setelah diberikan teknik short briefing secara rutin mengenai penyusunan RPP yang benar, materi pelajaran yang akan disampaikan dari siklus ke siklus. Siklus ke I mencapai rata-rata nilai 26,5 Siklus ke II mencapai 33. Disimpulkan bahwa pelaksanaan program yang rutin dan berkesinambungan merupakan kunci keberhasilan dalam melaksanakan tugas sebagai kepala sekolah dalam meningkatkan mutu pembelajaran di kelas. Pada upaya peningkatan kinerja guru melalui teknik Lesson Study secara kolaboratif dan rutin SD Negeri 13 Hutanamora ternyata mampu membentuk tenaga pendidik yang produktif/profesional dan mampu meningkatkan mutu pembelajaran. Kata kunci: kolaboratif; kinerja guru; lesson study